Intractable Fasting Hypoglycemia as a Manifestation of Hepatocellular Carcinoma - Justin J. Forde; Ofor Ewelukwa; Tony Brar; Roniel Cabrera (Case Reports in Hepatology)
Non-islet cell tumor hypoglycemia (NICTH) is a rare and serious paraneoplastic complication of both malignant and benign tumors to consider when evaluating fasting hypoglycemia, especially in the setting of liver diseases. We present a case of NICTH in a 54-year-old male with hepatocellular carcinoma (HCC) who presented with symptomatic intractable hypoglycemia (IH) after bowel preparation and fasting for screening upper endoscopy and colonoscopy.